Efektivitas Model Pembelajaran Project Based Learning dalam Meningkatkan Keterampilan Berpikir Kritis Siswa Sekolah SMA - Muhammad Bagas Hidayatullah; M Rizki Hidayatullah; Shigah Maulidina; Sani Safitri; Rani oktaviani (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to examine the effectiveness of the Project Based Learning (PjBL) model in improving high school students’ critical thinking skills, which are essential competencies in an era of information overload and demands for higher-order thinking. Conventional learning that remains teacher-centered often leads to low student engagement in the processes of analysis, evaluation, and argument construction. Through a qualitative method based on literature studies, this research analyzes empirical findings and theories that support the implementation of PjBL in the context of secondary education. The results show that PjBL is able to create more meaningful learning experiences through project activities that require students to identify problems, gather data, conduct in-depth analysis, collaborate, and present evidence-based solutions. This process not only strengthens critical thinking skills but also enhances students’ creativity, responsibility, and communication abilities. Although there are obstacles such as limited time, facilities, and the readiness of both teachers and students, institutional support and proper instructional planning can optimize its implementation.